2015
DOI: 10.1016/j.apcatb.2014.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Boron doped TiO2 catalysts for photocatalytic ozonation of aqueous mixtures of common pesticides: Diuron, o-phenylphenol, MCPA and terbuthylazine

Abstract: Additional Information:• This paper was accepted for publication in the journal Applied Cataly- TiO 2 and B-doped TiO 2 catalysts were synthesized using a sol-gel procedure. The 11 photocatalysts were characterized by ICP-EOS, N 2 adsorption-desorption, XRD, XPS, 12and DR-UV-Vis spectroscopy. Four recalcitrant pesticides (diuron, o-phenylphenol, 2-13 methyl-4-chlorophenoxyacetic acid (MCPA) and terbuthylazine) were subjected to 14 degradation by ozonation, photolytic ozonation, photocatalysis and photocatalyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(33 citation statements)
references
References 36 publications
0
32
0
1
Order By: Relevance
“…In photolytic (UV) and UV/H2O2 treatments the abatement of TBA is due mainly to direct photolysis or oxidation by hydroxyl radicals, generated from the photolysis of H2O2 (Alvarez et al 2016). Direct photolysis of 5 mg L -1 of TBA in a 250 mL reactor did not produce significant degradation (Quinones et al 2015), while the removal rate increased significantly in the UV254/H2O2 combined process.…”
Section: Uv and Uv/h2o2 Photodegradationmentioning
confidence: 99%
See 2 more Smart Citations
“…In photolytic (UV) and UV/H2O2 treatments the abatement of TBA is due mainly to direct photolysis or oxidation by hydroxyl radicals, generated from the photolysis of H2O2 (Alvarez et al 2016). Direct photolysis of 5 mg L -1 of TBA in a 250 mL reactor did not produce significant degradation (Quinones et al 2015), while the removal rate increased significantly in the UV254/H2O2 combined process.…”
Section: Uv and Uv/h2o2 Photodegradationmentioning
confidence: 99%
“…Solar-driven advanced oxidation processes, in which solar energy is used to activate a semiconductor, have recently attracted growing attention in water treatment applications (Quinones et al 2015). A 250 mL reactor was charged with an aqueous solution of TBA (5.0 mg L −1 ) and irradiated by a solar simulator, providing an irradiance at the solution level of 581 W m −2 .…”
Section: Solar Aopsmentioning
confidence: 99%
See 1 more Smart Citation
“…photocatalysis, of various emerging contaminants in natural water matrices. These studies reported high removal rates for pharmaceuticals and pesticides (He, Sutton, Rijnaarts, & Langenhoff, 2016;Prieto-Rodriguez et al, 2012;Quiñones, Rey, Alvarez, Beltr an, & Li Puma, 2015). Lab-scale combinations of subsurface flow CWs and photocatalysis were successful in the removal of these contaminants as well.…”
Section: Cw Design Considerationsmentioning
confidence: 95%
“…Therefore, there is a need for the development of visible light responsive photocatalyst. Recently many efforts have been taken to improve the visible light active photocatalytic properties of TiO 2 such as by doping with metals [10][11][12][13][14] and nonmetals [15][16][17][18], deposition of noble metals [19][20][21], surface fluorination [22] and controlling crystal facets [23], by creating heterojunction by coupling with other semiconductor materials having suitable band gap [24][25][26][27][28]. Design of nano structures having different morphologies like nanoflower [29], nanofibers [30], nanorod [31], coupling with carbanious materials like grapheme [32], carbon nanotube [33], and development of porous nanostructures [19] have also been proposed to increase visible light absorbance and to reduce the electron-hole pair recombination rate of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%